The hybridization effects of glass and carbon fibers on the mechanical properties of kenaf mat/epoxy composites - Malik, Khurshid; Ahmad, Faiz; Yunus, Nurul Azhani; Gunister, Ebru; Shaik Dawood, Mohd. Sultan Ibrahim; Ali, Saad; Mani, Catherine Sheila; Syahir, Muhammad; Leon Larry, Anselm (Taylor and Francis, 2022)
Kenaf mat/epoxy composite possesses low mechanical properties. The investigation examined the hybridization impact on the mechanical performance of kenaf mat/carbon/epoxy and kenaf mat/glass/epoxy hybrid composites. Pure and hybrid composites were fabricated using the vacuum-assisted resin infusion method. Density, tensile, flexural, interlaminar shear, and fracture toughness (Mode II) properties were tested according to the ASTM standards. The results showed that density increased around 10% for kenaf mat/carbon/ epoxy hybrid and 29% for kenaf mat/glass/epoxy hybrid compared to pure kenaf mat/epoxy composites. Kenaf mat/carbon/epoxy hybrid composites displayed approximately 529%, 497%, 512%, 1055%, 272%, and 443% improvement in the tensile strength, tensile modulus, flexural strength, flexural modulus, interlaminar shear strength (ILSS), and fracture toughness, respectively, compared to the pure kenaf mat/epoxy composite. Kenaf mat/ glass/epoxy hybrid composites displayed approximately 467%, 275%, 405%, 413%, 232%, and 366% improvement in the tensile strength, tensile modulus, flexural strength, flexural modulus, ILSS, and fracture toughness, respectively, compared to the pure kenaf mat/epoxy composite. Although the carbon fiber volume fraction was the lowest (17.23%) in hybrid kenaf mat/ carbon/epoxy composites compared to glass fiber (24.83%) in hybrid kenaf mat/glass/epoxy composites, the tensile, flexural, and interlaminar shear performance was higher in hybrid kenaf mat/carbon/epoxy composites than hybrid kenaf mat/glass/epoxy composites.